Smart locker with automatic light and security system - Adan, Nor Faezah; Aripim, Muhammad Khairul Izuddin; Mohd Zaim, Nurul Nadhirah; Zainal, Zulaikha Aina (Penerbit UTHM, 2020)
In the pursuit of modernization, there are various sophisticated technologies that can be applied in the necessities of life. Science and technology have advanced our life in many ways. It facilitates the process of industrialization as well as modernization of the world. It has blessed us with many sophisticated devices by facilitating our life and property. The password-based locking system is one of the modern electronic locks that have been introduced. Using the system as inspiration, this project is designed to make it easier for users to control the movements of the door of the locker according to the requirement that is opened and closed by entering the correct password through the 4x3 keypad.